Dependence of NPPS creates a targetable vulnerability in RAS-mutant cancers - Xia Rui-xue; Zou Pei-chen; Xie Jun-ting; Tang Ya-bin; Gong Miao-miao; Fan Fu; Aihemaiti Ayinazhaer; Liu Yu-qing; Shen Ying; Zhou Bin-bing S.; Zhu Liang; Lei Hui-min (Acta Pharmacologica Sinica, 2025)
RAS is the most frequently mutated oncoprotein for cancer driving. Understanding of RAS biology and discovery of druggable lynchpins in RAS pathway is a prerequisite for targeted therapy of RAS-mutant cancers. The recent identification of KRASG12C inhibitor breaks the “undruggable” curse on RAS and has changed the therapy paradigm of KRAS-mutant cancers. However, KRAS mutations, let alone KRASG12C mutation, account for only part of RAS-mutated cancers. Targeted therapies for cancers harboring other RAS mutations remain the urgent need. In this study we explored the pivotal regulatory molecules that allow for broad inhibition of RAS mutants. By comparing the expression levels of nucleotide pyrophosphatase (NPPS) in a panel of cell lines and the functional consequence of increased NPPS expression in RAS-mutant cells, we demonstrated that cancer cells with various kinds of RAS mutations depended on NPPS for growth and survival, and that this dependence conferred a vulnerability of RAS-mutant cancer to treatment of NPPS inhibition. RAS-mutant cells, compared with RAS-wildtype cells, bored and required an upregulation of NPPS. Transcriptomics and metabolomics analyses revealed a NPPS-dependent hyperglycolysis in RAS-mutant cells. We demonstrated that NPPS promoted glucose-derived glycolytic intermediates in RAS-mutant cells by enhancing its interaction with hexokinase 1 (HK1), the enzyme catalyzing the first committed step of glycolysis. Pharmacological inhibition of NPPS-HK1 axis using NPPS inhibitor Enpp-1-IN-1 or HK1 inhibitor 2-deoxyglucose (2-DG), or genetic interfere with NPPS suppressed RAS-mutant cancers in vitro and in vivo. In conclusion, this study reveals an unrecognized mechanism and druggable lynchpin for modulation of pan-mutant-RAS pathway, proposing a new potential therapeutic approach for treating RAS-mutant cancers.